2020
DOI: 10.1159/000506677
|View full text |Cite
|
Sign up to set email alerts
|

A Biobank of Stem Cells of Human Exfoliated Deciduous Teeth: Overview of Applications and Developments in Brazil

Abstract: A biobank is an organized collection of biological human material and its associated information stored for research according to regulations under institutional responsibility, without commercial purposes, being a mandatory and strategical activity for research, regenerative medicine, and innovation. Stem cells have largely been employed in research and frequently stored in biobanks, which have been used as an essential source of biological materials. Stem cells of human exfoliated deciduous teeth (SHED) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
2
0
3
Order By: Relevance
“…[11,12] SHED, which originate from the neural crest, are easy to harvest and establish a stem cell bank, safe to use, and have no ethical consequences, thus becoming an attractive source for cell-based or cell-free therapy. [15] Furthermore, in previous study on retinal degeneration, SHED themselves did not replace injured photoreceptors, but exerted therapeutic effects by paracrine secreta. [16] In this case, we extracted apoVs derived from SHED and validated the therapeutic effects of apoVs in murine ischemic retinopathy models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] SHED, which originate from the neural crest, are easy to harvest and establish a stem cell bank, safe to use, and have no ethical consequences, thus becoming an attractive source for cell-based or cell-free therapy. [15] Furthermore, in previous study on retinal degeneration, SHED themselves did not replace injured photoreceptors, but exerted therapeutic effects by paracrine secreta. [16] In this case, we extracted apoVs derived from SHED and validated the therapeutic effects of apoVs in murine ischemic retinopathy models.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] They have unique properties including a noninvasive and accessible method of harvesting from exfoliation. [ 15 ] What's more, because they originate from the neural crest, SHED are theoretically to possess a better capacity in neural supporting, which has been investigated in retinal degeneration. [ 16 ] It has been confirmed that SHED secrete neurotrophic factors, cytokines, and chemokines, which are benefit for repairing injured axons, [ 17 ] regulating angiogenesis, [ 18 ] and resisting inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Além dos BDHs, foram desenvolvidos os Biobancos de Dentes Humanos, que são serviços sem fins lucrativos para a coleta, processamento, armazenamento e distribuição de amostras e dados biológicos humanos, e informações associadas, para fins de pesquisa e diagnóstico, conforme regulamento ou normas técnicas, éticas e operacionais pré-definidas, sob responsabilidade e gerenciamento institucional dos materiais armazenados (Ministério da Saúde, 2011;Medeiros et al, 2020;Zalaf et al, 2020;Gebauer et al, 2021;Sivolella et al, 2022).…”
Section: Introductionunclassified
“…Os Biobancos têm grande importância no armazenamento e manipulação de células-tronco, que têm sido utilizadas como fonte essencial de materiais biológicos (Machado & Garrido, 2014;Zalaf et al, 2020;Sivolella et al, 2022), e podem ser obtidas da polpa dentária, osso medular e papila apical, de dentes decíduos esfoliados humanos e permanentes (Campanella, 2018;Mozaffari et al, 2019;Alomar et al, 2020;Zalaf et al, 2020). As células-tronco apresentam elevada capacidade de regeneração, reparo e reposição de tecidos danificados ou perdidos, e estão prontamente e facilmente disponíveis, sendo um recurso promissor na odontologia e medicina regenerativa em geral (Pereira, 2012;Machado & Garrido, 2014;Campanella, 2018;Zalaf et al, 2020;Gebauer et al, 2021). Ainda, podem ser importantes arquivos genéticos, visto que dentes são fontes de DNA e possuem informações genéticas do indivíduo, facilitando um processo de reconhecimento (Miranda & Bueno, 2012;Machado & Garrido, 2014), auxiliando a Odontologia Forense nas pesquisas com DNA e na identificação humana (Endo et al, 2017).…”
Section: Introductionunclassified
“…치주질환과 심혈관질 환, 당뇨, 폐렴, 종양, 치매 등 다양한 전신질환이 연관성이 있다는 연구 결과들이 활발히 생성되고 있는 만큼 치태와 치은 열구액 검체는 구강질환뿐만 아니라 전신질환의 병인을 밝히 거나 진단법을 찾는데 기여할 것으로 기대된다 [28][29][30][31] . 중간엽 줄기세포(mesenchymal stem cells, MSCs)는 치아 및 치아주위조직에서 가공할 수 있는 대표적인 이차자원으로 많은 치아 전문 인체자원은행에서 MSCs의 배양을 중요 자원 으로 내세우고 있다 [32][33][34] . MSCs는 성체의 기질 조직에서 분리한 줄기세포로 골세포, 연골세포, 지방세포 및 근육세포 등 다양 한 결합조직 세포로 분화할 수 있는 다분화능(multipotent) 세 포들이다 35) .…”
unclassified